2013
DOI: 10.1016/j.neulet.2012.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin and (S)-pregabalin decrease intracellular d-serine concentrations in PC-12 cells

Abstract: The effects of gabapentin (GBP) and (S)-pregabalin (PGB) on the intracellular concentrations of D-serine and the expression of serine racemase (SR) in PC-12 cells were determined. Intracellular D-serine concentrations were determined using an enantioselective capillary electrophoresis assay with laser-induced fluorescence detection. Increasing concentrations of GBP, 0.1 – 20 μM, produced a significant decrease in D-serine concentration relative to control, 22.9 ± 6.7% at 20 μM (*p < 0.05), with an IC50 value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
(49 reference statements)
2
13
0
Order By: Relevance
“…Indeed, previous studies in our laboratory have indicated that the incubation of PC-12 cells with increasing concentrations of methyllycaconitine or ( R,S )-dehydroxynorketamine decreases the intracellular concentration of the NMDAR co-agonist D-serine, a product of SR-mediated racemization of L-serine, despite higher expression of m-SR 14 . A similar decrease in intracellular D-serine concentrations was observed after incubation of PC-12 cells with the voltage-gated calcium channel α 2 δ inhibitors gabapentin and (S)-pregabalin 21 , which are used in the treatment of neuropathic pain, without impacting on m-SR protein level. The inhibition of SR activity has also been associated with a decrease in NMDAR activity, and SR inhibitors are being explored for use in the treatment of some CNS disorders 22,23 .…”
Section: Discussionsupporting
confidence: 58%
“…Indeed, previous studies in our laboratory have indicated that the incubation of PC-12 cells with increasing concentrations of methyllycaconitine or ( R,S )-dehydroxynorketamine decreases the intracellular concentration of the NMDAR co-agonist D-serine, a product of SR-mediated racemization of L-serine, despite higher expression of m-SR 14 . A similar decrease in intracellular D-serine concentrations was observed after incubation of PC-12 cells with the voltage-gated calcium channel α 2 δ inhibitors gabapentin and (S)-pregabalin 21 , which are used in the treatment of neuropathic pain, without impacting on m-SR protein level. The inhibition of SR activity has also been associated with a decrease in NMDAR activity, and SR inhibitors are being explored for use in the treatment of some CNS disorders 22,23 .…”
Section: Discussionsupporting
confidence: 58%
“…This inhibition lowers intracellular Ca 2+ , which, in turn, reduces the magnitude of Ca 2+ -activated SR and consequently the intracellular D-Ser concentrations. A similar reduction in intracellular D-Ser concentration was observed after incubation with gabapentin and ( S )-pregabalin, which reduce intracellular Ca 2+ concentrations via inhibition of the α 2 -δ subunit of voltage-gated calcium channels [24]. Based upon these observations and the recent report identifying a relationship between reduced D-Ser concentrations and attenuated NMDA receptor activity in rat and mouse models [22], it is reasonable to assume that a ( 2S,6S )-HNK-associated reduction in D-Ser production should also result in reduced NMDA receptor activation and associated neurotoxicity, synaptic death and depression.…”
mentioning
confidence: 68%
“…PC-12 cells were utilized here because they serve as a relevant in vitro model system for primary neuronal cells (Greene and Tischler 1976; Vignali et al 1996). They have been widely used to study voltage-gated Ca 2+ channels (Singh et al 2013; Zhang et al 2012) and effects of Mn 2+ exposure on these cells (Kwik-Uribe et al 2003; Reaney et al 2002; Zheng and Zhao 2001). Following withdrawal of doxycycline (Dox) from the medium, PC-12 cells were differentiated with nerve growth factor (NGF, R&D Systems 1156-NG/CF).…”
Section: Methodsmentioning
confidence: 99%